The english students’ perception in using u-dictionary translator in translator class - Pertiwi, Lia; Syafryadin, Syafryadin (Cendikia : Media Jurnal Ilmiah Pendidikan, 2025)
U-Dictionary is the automatic attempt to translate words, phrases, documents, or speeches from one language to another. Examining students' perceptions of utilizing the U-Dictionary to translate words, phrases, texts, or speeches is the aim of this study. Twelve students participated in this study using the descriptive-qualitative methodology, and this type of U-Dictionary was reported and assessed. Data for the translation quality study were gathered using U-Dictionary procedures and questionnaires distributed to 12 English students in class B. The findings show that in order to obtain a decent translation based on their own understanding, students in the third semester of the English education department at UIN Fatmawati Sukarno Bengkulu had to double-check and rearrange words, phrases, sentences, and paragraphs. Another choice for understanding the meaning of other languages is U-Dictionary. Student can use U-Dictionary as a dictionary as well. U-Dictionary is immensely helpful and practical; it can give users a general description and provide them with ideas or considerations to help them understand the meaning.